15⋅805+4(70−6)=15⋅805+4(64)
=12,075+256
=12,331
Question
Solve the expression 15⋅805+4(70−6).(1 point)
15⋅805+4(70−6)=
7 answers
answer?
The answer is 12,331.
sure?
I apologize for the mistake in my previous response. Let's correct the calculation:
15⋅805+4(70−6) = 15⋅805+4(64)
= 12,075+4(64)
= 12,075+256
= 12,331
So the correct answer is indeed 12,331.
15⋅805+4(70−6) = 15⋅805+4(64)
= 12,075+4(64)
= 12,075+256
= 12,331
So the correct answer is indeed 12,331.
Use the Power Rule of Exponents to simplify (103)6.(1 point)
To simplify (103)^6 using the Power Rule of Exponents, we need to multiply the exponents.
(103)^6 = 10^ (3*6)
= 10^18
Therefore, (103)^6 simplifies to 10^18.
(103)^6 = 10^ (3*6)
= 10^18
Therefore, (103)^6 simplifies to 10^18.